Inexpensive Reconstruction and Rendering of Realistic Roadside Landscapes. (12th February 2014) - Andújar, C.; Chica, A.; Vico, M. A.; Moya, S.; Brunet, P.
<x xml:space="preserve">Abstract</x> In this paper, we present an inexpensive approach to create highly detailed reconstructions of the landscape surrounding a road. Our method is based on a space‐efficient semi‐procedural representation of the terrain and vegetation supporting high‐quality real‐time rendering not only for aerial views but also at road level. We use a vehicle‐mounted camera to capture a collection of photographs along selected road stretches. We integrate the point clouds extracted from these photographs with a low‐resolution digital terrain model through a novel algorithm which is robust against noise and missing data. We pre‐compute plausible locations for trees through an algorithm which takes into account perceptual cues. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>